2014
DOI: 10.1177/1533317514535334
|View full text |Cite
|
Sign up to set email alerts
|

Medical Resource Value Appraisal for Leucojum aestivum in Turkey

Abstract: In this study, we investigate the medical and economical value of Leucojum aestivum. Leucojum aestivum contains the alkaloid galanthamine, which is one of the main active substances in Reminyl, a commonly used drug for the treatment of Alzheimer's disease (AD). In this analysis, we estimate that there are 13 million mild to moderate patients with Alzheimer's who use Reminyl. Our results suggest that the market change value of L aestivum required for 1 unit of Reminyl is US$62. The value of total change of gala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…Some plants are used extensively by the public in the study area. The most important of these is the Leucojum aestivum (Göl Soğanı) plant [15]. As a result of scientific studies, this plant; The emergence of its usability in the treatment of Alzheimer's disease has further increased the public's demand for this plant.…”
Section: Abbreviationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some plants are used extensively by the public in the study area. The most important of these is the Leucojum aestivum (Göl Soğanı) plant [15]. As a result of scientific studies, this plant; The emergence of its usability in the treatment of Alzheimer's disease has further increased the public's demand for this plant.…”
Section: Abbreviationsmentioning
confidence: 99%
“…CR, 2 EN, 15 VU, 2 NT and 8 LC. 5 families were the largest in terms of number of taxa included in the numerical distribution are as fallows; Orchidaceae (43), Asparagaceae (37), Amaryllidaceae (21), Iridaceae (17), Ranunculaceae (15).…”
Section: Mehmet Sağiroglumentioning
confidence: 99%
“…It grows with bulbs or seeds and usually blooms from March to June. The number of flowers per plant usually ranges from 1 to 5.2 (Atay, 1996;Cherkasov and Tolkachev, 2002;De Groot et al, 2002;Diop et al, 2007;Demir, 2014) In the studies conducted so far, chemical properties of alkaloids found in L. aestivum have been focused. Investigations on sustainable production and medical resource value of medicinal plants remain limited.…”
Section: Introductionmentioning
confidence: 99%
“…As the alkaloid is obtained from natural sources, there is a need for sustained production of the active principle, together with sustained cultivation of the species. The study conducted by Demir (2014) on the use of galanthamine from L. aestivum showed that the cost of producing drugs used to treat Alzheimer's disease is relatively high. Considering the findings of Demir (2014) and also the climate change (IPCC, 2014), it is important to know, monitor and protect the natural populations of L. vernum and L. aestivum, and to develop sustainable cultivation of both species, where it is necessary.…”
Section: Introductionmentioning
confidence: 99%
“…The study conducted by Demir (2014) on the use of galanthamine from L. aestivum showed that the cost of producing drugs used to treat Alzheimer's disease is relatively high. Considering the findings of Demir (2014) and also the climate change (IPCC, 2014), it is important to know, monitor and protect the natural populations of L. vernum and L. aestivum, and to develop sustainable cultivation of both species, where it is necessary. It is known that plant populations Acta Biologica Marisiensis respond slowly to changes in the environment, primarily through morphological, physiological, and biochemical responses.…”
Section: Introductionmentioning
confidence: 99%